Characterization of Antibiotic Resistance Genes from Lactobacillus Isolated from Traditional Dairy Products. Issue 3 (9th February 2017) - Guo, Huiling; Pan, Lin; Li, Lina; Lu, Jie; Kwok, Laiyu; Menghe, Bilige; Zhang, Heping; Zhang, Wenyi
Abstract: Lactobacilli are widely used as starter cultures or probiotics in yoghurt, cheese, beer, wine, pickles, preserved food, and silage. They are generally recognized as safe (GRAS). However, recent studies have shown that some lactic acid bacteria (LAB) strains carry antibiotic resistance genes and are resistant to antibiotics. Some of them may even transfer their intrinsic antibiotic resistance genes to other LAB or pathogens via horizontal gene transfer, thus threatening human health. A total of 33 Lactobacillus strains was isolated from fermented milk collected from different areas of China. We analyzed (1) their levels of antibiotic resistance using a standardized dilution method, (2) their antibiotic resistance gene profiles by polymerase chain reaction (PCR) using gene‐specific primers, and (3) the transferability of some of the detected resistance markers by a filter mating assay. All Lactobacillus strains were found to be resistant to vancomycin, but susceptible to gentamicin, linezolid, neomycin, erythromycin, and clindamycin. Their susceptibilities to tetracycline, kanamycin, ciprofloxacin, streptomycin, quinupristin/dalfopristin, trimethoprim, ampicillin, rifampicin, and chloramphenicol was different. Results from our PCR analysis revealed 19 vancomycin, 10 ciprofloxacin, and 1 tetracycline‐resistant bacteria that carried the van (X), van (E), gyr (A), and tet (M) genes, respectively. Finally, no transferal of the monitored antibiotic resistance genes was observed in the filter mating assay. Taken together, our study generated the antibiotic resistance profiles of some milk‐originated lactobacilli isolates and preliminarily assessed their risk of transferring antibiotic gene to other bacteria. The study may provide important data concerning the safe use of LAB.